SUBSTANTIATION OF THE EFFICIENCY OF OIL AND GAS INJECTION TECHNOLOGIES IMPLEMENTATION - Panevnyk, Denys (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2023)
An algorithm for substantiating the economic feasibility of using ejection technologies when drilling operational oil and gas wells has been developed. The proposed method of determining the effectiveness of the implementation of ejection technologies in drilling is based on the assessment of the impact of the use of a jet pump on the amount of variable costs of the cycle of direct passage of the well. The advantages of using an overbite jet pump are realized in the implementation of technological operations of mechanical drilling and lowering and lifting works. It was established that the implementation of ejection technologies makes it possible to reduce the costs of mechanical drilling due to the increase in the speed of deepening wells and the reduction of the duration of the process. The use of an over-bit jet pump helps to increase the passage of the bit, reduces the number of bits required for drilling a given interval and the total cost. Reducing the required number of flights allows you to reduce the costs of lowering and lifting operations to replace the rock-crushing tool. It was established that the amount of variable costs associated with the deepening of an operational oil and gas well is inversely proportional to the mechanical speed of drilling and the passage of the bit. The coordinates of the point of intersection of the dependencies of variable costs associated with the deepening of an operational oil and gas well, obtained for the basic and advanced layout, determine the conditions for the feasibility of using ejection technologies.In the process of analyzing the ratios of the mechanical speeds of the well deepening and bit passages, characteristic cases were identified when justifying the economic feasibility of using ejection technologies. If the use of a jet pump provides an increase in the passage of the bit, a reduction in the costs associated with drilling is possible even with a decrease in the mechanical speed of deepening wells. In the case of a reduction in the passage of the bit when using ejection technologies, the mechanical speed of deepening wells with an over-bit jet pump should be greater than for the basic layout.